Effects of rs958804 and rs7858836 single‐nucleotide polymorphisms of the ASTN2 gene on pain‐related phenotypes in patients who underwent laparoscopic colectomy and mandibular sagittal split ramus osteotomy - Rie Inoue; Daisuke Nishizawa; Junko Hasegawa; Kyoko Nakayama; Ken‐ichi Fukuda; Tatsuya Ichinohe; Tsutomu Mieda; Miki Tsujita; Hideyuki Nakagawa; Akira Kitamura; Hiroyuki Sumikura; Kazutaka Ikeda; et al. (Neuropsychopharmacology Reports, 2021)
Abstract Background Opioids are widely used as effective analgesics, but opioid sensitivity varies widely among individuals. The underlying genetic and nongenetic factors are not fully understood. Based on the results of our previous genome‐wide association study, we investigated the effects of single nucleotide polymorphisms (SNPs) of the astrotactin 2 (ASTN2) gene on pain‐related phenotypes in surgical patients. Methods We investigated the effects of two SNPs, rs958804 T/C and rs7858836 C/T, of the ASTN2 gene on eight and seven pain‐related phenotypes in 350 patients who underwent laparoscopic colectomy (LAC) and 358 patients who underwent mandibular sagittal split ramus osteotomy (SSRO), respectively. In both surgical groups, intravenous fentanyl patient‐controlled analgesia (PCA) was used for postoperative analgesia, and 24‐hour postoperative PCA fentanyl use was the primary endpoint. Results The association analyses among the two SNPs and pain‐related traits showed that 24‐hour fentanyl use was significantly associated with the two SNP genotypes in both surgical groups. The Mann‐Whitney test showed that 24‐hour fentanyl use was lower in patients with the C allele than in patients with the TT genotype of the rs958804 T/C SNP (P = .0019 and .0200 in LAC and SSRO patients, respectively), and it was lower in patients with the T allele than in patients with the CC genotype of the rs7858836 C/T SNP (P = .0017 and .0098 in LAC and SSRO patients, respectively). Conclusion The two SNPs of the ASTN2 gene were consistently associated with fentanyl requirements after two different types of surgery. These findings may contribute to personalized pain control.